(untitled) (Journal of Science-Innovative Research in Uzbekistan, 2023)
The article contains a conclusion about that a complex of three interrelated components: modern content that is transmitted to students, active teaching methods and monitoring of educational results, as well as the availability of modern infrastructure to ensure the learning process – allows students to master technologies for teaching literature in modern school.